PENGARUH PEMBERIAN INFUSA DAUN KERSEN (Muntingia calabura L.) TERHADAP KADAR GLUKOSA DARAH MENCIT PUTIH (Mus musculus) YANG DIBERI BEBAN GLUKOSA - mira febrina (Jurnal Penelitian Farmasi Indonesia, 2019)
A study on the effect of cherry leaf infusion (Muntingia calabura L.) on glucose levels of male white mice (Mus musculus) given glucose load. This study aims to see the effect of cherry leaf infusion (Muntingia calabura L.) to blood glucose levels of male white mice (Mus musculus) given glucose load as much as 0.65ml / 20gBB. This research used Oral Glucose Tolerance Test (TTGO) method. Animal experiments were divided into 6 groups. The negative control group was given only aquadest, the positive group was given metformin with the dosage of 1.3mg / 20gBB, the comparison group was given 0.65ml / 20gBB glucose solution, the treatment group was given cesen leaves infusion (Muntingia calabura L.) with concentration 5, 10 and 20 %. After each test animal was given 30 minutes treatment then given glucose 0.65ml / 20gBB orally. Then measured blood glucose levels of mice at minute 30-180. Based on the results of testing the infusion of kersen leaf (Muntingia calabura L.) showed that the concentrations of 5, 10 and 20% had decreased levels of white mice blood glucose (Mus musculus) with normal control. However, the results of the two-way ANOVA assay continued with the Post Hoc Tukey test showed that the concentration of 20% differed significantly with the concentrations of 5 and 10%. And the results obtained also indicate that the duration of administration may affect the decrease in blood glucose levels of mice (p <0.05).